OFFICIAL OR ORIGINAL: IMPLEMENTING RESOURCE DESCRIPTION AND ACCESS (RDA) IN ACADEMIC LIBRARIES AFTER THE 3R PROJECT [ARTICLE] - Santos, Mark Anthony A. (Nazarbayev University Library, 2021)
Since 2010, Resource Description and Access (RDA) has been used by many libraries around the world for the description of information resources. As of May 2021, two versions of RDA are available for use: the “original” and the “official” versions. With the release of the “official” version of RDA on December 15, 2020, libraries currently utilizing RDA will be expected to undergo the necessary preparations to transition to the “official” version of RDA. Implementation dates of the “official” version of RDA is up to the libraries and communities, as recommended by the RDA Steering Committee. While the “original” version of RDA will still be available during this transition period, eventually it will no longer be accessible interactively. This paper presents a brief overview of the status of implementation of RDA and recommendations for transition to the “official” version of RDA
Keywords: Type of access: Open Access; library; EALC; Resource Description and Access